2020
DOI: 10.17263/jlls.851024
|View full text |Cite
|
Sign up to set email alerts
|

The awareness of ELL students about their 21st century skills

Abstract: This study investigates the 21st century skills of the third and fourth year students studying at the Department of English Language and Literature of two Turkish state universities. Additionally, this study reveals the levels of the 21st century skills of these students. To this end, a case study has been designed and conducted with 158 ELL students and 20 lecturers of the same department. The study has been conducted throughout the 2019-2020 academic year. In this study we review the related literature and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Similarly, Bedir (2019) found that English teacher candidates have a moderate level of awareness on 4Cs, and also Baran-Lucarz and Klimas (2020) revealed that the majority of EFL teacher candidates lack a clear knowledge of what 21st century abilities are. On the other hand, Irgatoğlu and Pakkan (2020) found the 21st century skills awareness levels of the students studying at the English Language and Literature department to be high. The students in the English Language and Literature department read more books, write more book reviews, reflect critically on the themes in the books they read, and discuss those themes in their classes with others, which may be the reasons that distinguish them from the students in the English Language Teaching Department.…”
Section: T2 the Most Effective 21st Century Skills In Eltmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, Bedir (2019) found that English teacher candidates have a moderate level of awareness on 4Cs, and also Baran-Lucarz and Klimas (2020) revealed that the majority of EFL teacher candidates lack a clear knowledge of what 21st century abilities are. On the other hand, Irgatoğlu and Pakkan (2020) found the 21st century skills awareness levels of the students studying at the English Language and Literature department to be high. The students in the English Language and Literature department read more books, write more book reviews, reflect critically on the themes in the books they read, and discuss those themes in their classes with others, which may be the reasons that distinguish them from the students in the English Language Teaching Department.…”
Section: T2 the Most Effective 21st Century Skills In Eltmentioning
confidence: 94%
“…At the tertiary level, it was concluded that undergraduate students studying in the English Language and Literature department were conscious of 21st century skills and most of them use the 21st century skills in their lives (Irgatoğlu & Pakkan, 2020). In the studies conducted to determine the 21st century skills of the students studying at the education faculties of the universities and the preservice teachers, there was a statistically significant difference in the perceptions of the prospective teachers about lifelong learning competencies according to the gender and the department they study (Evin-Gencel, 2013), teaching skills varied greatly depending on the department, academic success, private lesson experience, teaching practice, and gender (Tican & Deniz, 2018), prospective teachers had a level of agreement with the sub-dimensions of 21st century skills that is higher than moderate (Kan & Murat, 2018), pre-service teachers who received pedagogical formation education had 21st century skills at a sufficient level, and there were no significant difference between 21st century skills in terms of gender and department they study (Erten, 2019), and that digital storytelling helped primary school teacher candidates develop their 21st century competencies (Ciğerci, 2020).…”
Section: Cultural Awareness and Expressionmentioning
confidence: 99%
“…Having addressed the skills considered as those necessary to face the challenges posed by the 21st century, considered by Wagner (2008) as the 'Survival Skills', it is important to make reference to the instruments used to assess them, knowing that it is in the sphere of teaching and learning that we find greater emphasis in the most recent literature (Care et al, 2018;Irgatoğlu & Pakkan, 2020;Sondergeld & Johnson, 2019;Tican & Deniz, 2019), where scales and semi-structured interviews prevail. Skills are predominantly evaluated through interviews, observation, and mixed approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Algorithmic thinking is another crucial skill for today's corporate and educational settings. It involves planning the actions or course of action needed to achieve the desired objectives (Doleck et al, 2017;Irgatoglu and Pakkan, 2020). Digital literacy is also important in today's digital world (Kocak et al, 2021).…”
Section: Introductionmentioning
confidence: 99%